Trends in doctors' early career choices for general practice in the UK: longitudinal questionnaire surveys. - Lambert, T; Goldacre, M (2011)
BACKGROUND: The percentage of newly qualified doctors in the UK who want a career in general practice declined substantially in the 1990s. The English Department of Health expects that half of all doctors will become GPs. AIM: To report on choices for general practice made by doctors who qualified in 2000, 2002, 2005, 2008, and 2009. DESIGN AND SETTING: A structured, closed questionnaire about future career intentions, sent to all UK medical graduates. METHOD: Questionnaires sent 1 year after qualification (all cohorts) and 3 years after (all except 2008 and 2009). RESULTS: Percentages of doctors who expressed an unreserved first choice for general practice in the first year after qualification, in the successive five cohorts, were 22.2%, 20.2%, 23.2%, 21.3%, and 20.4%. Percentages who expressed any choice for general practice - whether first, second or third - were 46.5%, 43.4%, 52.6%, 49.5%, and 49.9%. Three years after qualification, an unreserved first choice was expressed, in successive cohorts, by 27.9%, 26.1%, and 35.1%. Doctors from newly established English medical schools showed the highest levels of choice for general practice. CONCLUSION: The percentage of doctors, in their first post-qualification year, whose first choice of eventual career was general practice has not changed much in recent years. By year 3 after qualification, this preference has increased in recent years. At years 1 and 3, the overall first choice for general practice is considerably lower than the required 50%, but varies substantially by medical school. In depth studies of why this is so are needed.